(untitled) (Research, Society and Development, 2022)
Surgical procedures are in the daily life of the dental surgeon and due to the longer maintenance of natural teeth by patients in relation to age, oral surgeries are becoming increasingly common in patients who use oral anticoagulants, so the dental surgeon must stay aware of the actions to be taken. This study aims to review the literature on the conduct to be taken in oral surgeries in patients who use anticoagulants continuously, evaluating the risk of discontinuing this medication and the risk of bleeding. For the construction of this work, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. The results of this research reveal that the continuation of drug therapy with warfarin in patients undergoing simple and atraumatic tooth extractions can be performed as long as the patient is in the appropriate therapeutic range analyzed through the INR. Regarding the extraction of invasive third molars, the procedure can be performed when the INR is up to 2.11, and your medical history is evaluated in detail, but more studies are needed for this type of procedure.